Mechanisms and roles of phagocytosis in Drosophila and Caenorhabditis elegans - Y Nakanishi; A Shiratsuchi (Invertebrate Survival Journal, 2006)
Our understanding of the humoral immune response in both vertebrates and invertebrates has dramatically deepened in the past decade. In contrast, many of the mechanisms and roles of the cellular immune response remain to be elucidated. Phagocytosis is at the center of the cellular responses in both innate and adaptive immunity. Targets of phagocytosis are either invading microbes or altered self, that is, own cells that have become dispensable or harmful. The selective recognition and engulfment of target cells by phagocytes are achieved through the specific binding of receptors of phagocytes to ligands present on the surface of the target cells. However, these phagocytosis receptors and ligands are still being identified. The fundamental mechanism of phagocytosis appears to be the same in vertebrates and invertebrates, but whether or not genes are evolutionally conserved has yet to be determined.